The Effect of Competence, Compensation and Discipline on Partners Employees Performance at Central Statistics Agency - Yohanes Susanto; Astri Riance (Eduvest - Journal of Universal Studies, 2021)
The purpose of this research is to analyze the effect of competence, compensation and discipline variables on the performance of partners employees at Central Statistics Agency (BPS) of Lubuklinggau City. The population of this work were 163 respondents and a survey based quantitative method was used in this work. The Structure Equation Modell (SEM) statistical tool then utilized for data analysis purposes. The results showed that the sub-structure of the employee discipline variable was influenced by the level of competence and compensation. Structurally, the performance of the partners employees of BPS of Lubuklinggau City was influenced by competence, compensation and discipline. However, compensation had the most dominant influence compared to the other two variables. This illustrates that the higher the compensation provided by the organization to its employees, will have an impact on improving the performance of its employees.